Hot Flashes and Cardiovascular Disease Risk Indices Among Women With HIV. (12th January 2021) - Toribio, Mabel; Fulda, Evelynne S; Chu, Sarah M; Drobni, Zsofia D; Awadalla, Magid; Cetlin, Madeline; Stanley, Takara L; North, Crystal M; Nelson, Michael D; Jerosch-Herold, Michael; Szczepaniak, Lidia S; Burdo, Tricia H; et al.
Abstract: Women with HIV (WWH) transitioning through menopause have heightened cardiovascular disease (CVD) risk. In the general population, hot flash burden relates to CVD risk indices. We found higher hot flash burden among women with vs without HIV. Further, among WWH, hot flash burden related to select CVD risk indices. ClinicalTrials.gov Registration: NCT02874703.